Enhancing Entrepreneurial Attitudes through Project-Based Learning: A Study on Universitas Jambi Graduates - Mayasari Mayasari; Ervan Johan Wicaksana; Dara Mutiara Aswan; Tri Wahyu Hardaningrum (STAI Hubbulwathan Duri, 2025)
This study investigates the effectiveness of Project-Based Learning (PjBL) in enhancing entrepreneurial attitudes among graduates of Universitas Jambi. It focuses on how experiential and collaborative PjBL activities contribute to developing key entrepreneurial traits such as proactiveness, creativity, resilience, and adaptability—beyond traditional classroom approaches. Using a Design-Based Research (DBR) framework, this mixed-methods study combines quantitative and qualitative approaches. Data were collected from 384 final-year students through surveys, observations, and interviews. Quantitative analysis employed a paired-sample t-test, while qualitative insights were gathered through in-depth interviews with students and faculty. Statistical findings reveal that PjBL significantly improves entrepreneurial attitudes. The implementation of PjBL showed a t-value of 7.966 for entrepreneurial effectiveness, and a t-value of 2.637 for the influence of entrepreneurial attitude quality—both exceeding the critical t-value (1.6252) at a 5% significance level. These results confirm the positive impact of PjBL on entrepreneurial mindset development. Supporting factors such as faculty mentorship and access to business incubators further strengthened these outcomes. The study concludes that PjBL is an effective pedagogical strategy for fostering entrepreneurial competencies in higher education. It enables students to apply entrepreneurial principles through real-world problem solving, teamwork, and critical reflection. Future studies should explore longitudinal impacts on career outcomes and the integration of digital tools and industry partnerships to maximize PjBL’s effectiveness in entrepreneurship education.